Effects of a reactive oxygen species generator, napabucasin (BBI608), on tolerability, safety, pharmacokinetics, and QT/QTc interval in healthy volunteers - Naoto Noda (Wiley, 2021)
Abstract This study examined the safety, tolerability, and pharmacokinetics (PK) of napabucasin in healthy Asian and non‐Asian participants and investigated the potential for QT/QTc interval prolongation. This five‐part (A–E) study proceeded in a stepwise manner, unless stopping criteria were met. Parts A–D were randomized, double‐blind, placebo‐controlled, and included healthy Asian male and female and non‐Asian male participants. PK parameters were measured following single‐dose napabucasin (80–1200 mg) in the fasted or fed state (Part D). Potential QT/QTc interval prolongation was assessed using digital 12‐lead electrocardiogram (Parts B and C). Part E was open‐label, and examined the PK of single‐dose napabucasin (240–720 mg) in healthy non‐Asian males. Safety and tolerability were measured in Parts A–E. Changes from baseline in the Fridericia‐corrected QT interval (ΔQTcF) and other electrocardiogram parameters were analyzed using a linear mixed‐effects model. Napabucasin was well‐tolerated across the study (n = 70), and no serious adverse events or significant safety issues were reported when administered with or without food. The most frequent treatment‐emergent adverse events were diarrhea and abdominal pain, and these were mild in severity. No prolongation of the QTcF interval was reported following single‐dose napabucasin (240–1200 mg) and changes in other cardiac parameters were negligible. The PK profile of napabucasin was consistent with earlier studies. Single‐dose napabucasin was tolerated in healthy male and female participants, and no significant safety (including no QTcF prolongation) or tolerability issues were identified, irrespective of food intake. Clinical studies of napabucasin in advanced cancers are ongoing.